2011
DOI: 10.1159/000333274
|View full text |Cite
|
Sign up to set email alerts
|

<i>BRAF</i> Mutation Testing of Thyroid Fine-Needle Aspiration Specimens Enhances the Predictability of Malignancy in Thyroid Follicular Lesions of Undetermined Significance

Abstract: Background/Objective: The Bethesda 2007 Thyroid Cytology Classification defines atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) as a heterogeneous category of cases that are neither convincingly benign nor sufficiently atypical for a diagnosis of follicular neoplasm or suspicious for malignancy. At our institution, we refer to these cases as ‘indeterminate’ and they are further subclassified into two categories. BRAF mutation occurs in 40–60% of papillary thyroid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 42 publications
2
44
0
1
Order By: Relevance
“…This can be connected with the low prevalence of PTC in this cytological category and higher prevalence of FTC that are BRAF V600E negative. Moreover, in all the studies it was highlighted that high positive predictive value in the detection of cancer can reach 100% [25][26][27]. Results from the presented study are concordant with cited reports.…”
Section: Discussionsupporting
confidence: 89%
“…This can be connected with the low prevalence of PTC in this cytological category and higher prevalence of FTC that are BRAF V600E negative. Moreover, in all the studies it was highlighted that high positive predictive value in the detection of cancer can reach 100% [25][26][27]. Results from the presented study are concordant with cited reports.…”
Section: Discussionsupporting
confidence: 89%
“…8 Adeniran et al 1 suggested that BRAF mutation testing can be used with high specificity to predict malignancy in thyroid follicular lesions of undetermined significance. Similarly, we showed that BRAF expression was significantly higher in our FVPC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the FVPC, BRAF mutation was reported in only 5-20% of cases, 8 and there is limited study on the role of BRAF expression in differentiating between follicular lesions of thyroid. 1,4 GAL-3 is a beta-galactosylbinding lectin which is involved in regulating cell-cell and cellmatrix interactions. Galectin-3 expression has been proposed to be a reliable molecular marker of FC 9 and PC, 10 and suggested be used to differentiate benign from malignant thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these discrepancies in terms of choice of methodology, there are additional studies that suggest that analysis at a molecular level provides almost the same results as with a second TFNAB (2,14). A view that has recently gained momentum is a consensus approach mentioned by Jing and colleagues (15).…”
Section: Discussionmentioning
confidence: 99%